Epigenetic suppression of creatine kinase B in adipocytes links endoplasmic reticulum stress to obesity-associated inflammation - Gianluca Renzi; Ivan Vlassakev; Mattias Hansen; Romane Higos; Simon Lecoutre; Merve Elmastas; Ondrej Hodek; Thomas Moritz; Lynn M. Alaeddine; Scott Frendo–Cumbo; Ingrid Dahlman; Alastair Kerr; et al. (Molecular Metabolism)
In white adipose tissue, disturbed creatine metabolism through reduced creatine kinase B (CKB) transcription contributes to obesity-related inflammation. However, the mechanisms regulating CKB expression in human white adipocytes remain unclear. By screening conditions perturbed in obesity, we identified endoplasmic reticulum (ER) stress as a key suppressor of CKB transcription across multiple cell types. Through follow-up studies, we found that ER stress through the IRE1–XBP1s pathway, promotes CKB promoter methylation via the methyltransferase DNMT3A. This epigenetic change represses CKB transcription, shifting metabolism towards glycolysis and increasing the production of the pro-inflammatory chemokine CCL2. We validated our findings in vivo, demonstrating that individuals living with obesity show an inverse relationship between CKB expression and promoter methylation in white adipocytes, along with elevated CCL2 secretion. Overall, our study uncovers a regulatory axis where ER stress drives inflammation in obesity by reducing CKB abundance, and consequently altering the bioenergetic state of the cell.